â€œPENGARUH IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS, LINGKUNGAN PENGENDALIAN DAN SPIRITUALITAS TERHADAP PENCEGAHAN FRAUDâ€ - Pratiwi, Nadia; Irwansyah, Irwansyah (JURNAL ILMIAH EDUNOMIKA, 2024)
Fraud is an intentional act. This research aims to determine the effect of implementing sustainable development goals, control environment, and spirituality on fraud prevention. The sample for this research was all village officials in Talang Empat sub-district, Central Bengkulu. The research method is quantitative, and uses SmartPLS 3.00 software. The results of this research explain that the implementation of sustainable development goals, control environment and spirituality have a significant positive effect on fraud prevention.